Plummer-Vinson syndrome: A case series - S T Kavya; H R Sanjay Kumar; T Sridevi; Devapriya Rejeev (Wolters Kluwer Medknow Publications, 2020)
Plummer-Vinson syndrome (PVS), also known as Paterson-Brown-Kelly syndrome, is characterized by a triad of dysphagia, upper esophageal web, and iron deficiency anemia. It predominantly affects middle-aged females. The postcricoid webs are associated with a higher risk of squamous cell carcinoma; therefore, timely diagnosis and treatment is important. Herein, we report three cases of PVS.